Generalized eczematous rash in a patient with shoe contact dermatitis: a case report - Alotaibi, Moteb K. (International Journal of Advances in Medicine, 2019)
The id reaction, which is also known as autoeczematisation or autosensitisation dermatitis, refers to the acute development of dermatitis at a site distant from the site of the primary inflammatory cutaneous reaction. Many stimuli have been reported as causes of id reactions, including allergic contact dermatitis. The exact prevalence of id reaction is unknown, however, id reactions have been found to occur in 4%-5% of cases of dermatophyte infections and in up to 37% of patients with stasis dermatitis. This condition has no known predilection for any race, sex or age groups. Shoe dermatitis is a type of contact dermatitis developed following the contact of the foot’s skin with shoe’s parts that contain different chemical substance that harbor the potentiality to be an immune trigger. Among the potential allergens, rubber is found to be the most common shoe-related allergen reported in the literature. Other known allergens include: cements, dichromats used in tanning, dyes, anti-mildew agents, formaldehyde, and nickel eyelets or nickel arch supports. The pathogenesis of allergic contact dermatitis is a type IV, delayed-type immune response that provoked by cutaneous contacts with different material that have the ability to stimulate antigen-specific T-helper 1 (TH1) in a sensitized individual. The clinical presentation of id reaction includes acute onset of pruritic erythematous eruption with symmetrical distribution that follows the primary dermatitis by one to two weeks. Authors report a 27-year-old male who presented with generalized, symmetric pruritic and eczematous eruption following localized shoe dermatitis.